Development of a problem-based e-LKPD to improve students' cognitive learning outcomes on kingdom Monera - Al Laros, Vizza Az Zahra; Priantari, Ika; Prafitasari, Aulya Nanda; Anantyarta, Primadya (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Learning on Monera material shows low learning outcomes due to the abstract and complex characteristics of the material and the limited learning resources used. This study aims to develop an E-LKPD based on Problem-Based (PBL) on Monera material. The research method used is development research with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The study population consisted of 360 grade X students at SMAN 3 Jember. The sample was selected through a purposive sampling technique consisting of a small group experiment with 6 students and a large group experiment with 36 students. The research instruments included expert validation sheets, integrated learning outcome tests of cognitive levels C1-C6 in the form of pre-tests and post-tests, E-LKPD, and student response questionnaires. Data were collected through observations, tests, and questionnaires, and analyzed using quantitative and qualitative descriptive methods. The results of the study indicate that the developed product is proven to be valid, effective, and practical in improving students' cognitive abilities, with an N-gain score of 0.72 in a small-scale trial which is included in the effective category and 0.82 in a large-scale trial which is included in the very effective category, as well as a practicality level of 86.51% and 80% respectively which are in the very practical category. Therefore, the developed E-LKPD can serve as an alternative digital learning resource for teaching abstract biology topics at the high school level.